2016
DOI: 10.1007/s10811-016-0853-0
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen, antioxidant, and bactericide capacities of phlorotannins from the brown macroalga Halidrys siliquosa

Abstract: 00000 ăWOS:000390090300038International audienceThe present study focused on a brown macroalga (Halidrys siliquosa), with a particular emphasis on polyphenols and their associated biological activities. Two fractions were obtained by liquid/liquid purification from a crude hydroethanolic extract: (i) an ethyl acetate fraction and (ii) an aqueous fraction. Total phenolic contents and antioxidant activities of extract and both fractions were assessed by in vitro tests (Folin-Ciocalteu test, 2,2-diphenyl-1-picryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 61 publications
1
50
0
5
Order By: Relevance
“…The results indicated that our extraction method was more efficient [33,34,35,36]. In addition, the DRSA of ethyl acetate fractions of S. fusiforme in our study (IC50 14.61 ± 0.56 μg·mL −1 ) was higher than those of some Sargassaceae species including Halidrys siliquosa (IC50 0.020 ± 3.54 × 10 −4 mg·mL −1 ) [28] and Cystoseira nodicaulis (IC50 14.00 ± 0.04 μg·mL −1 ). When compared with other brown seaweeds, it was lower than that of F. vesiculosus (IC50 4.00 ± 0.01 μg·mL −1 ), similar to that of Himanthalia elongate (IC50 14.00 ± 0.04 μg·mL −1 ), and stronger than that of F. serratus (IC50 14.00 ± 0.04 μg·mL −1 ).…”
Section: Resultsmentioning
confidence: 81%
“…The results indicated that our extraction method was more efficient [33,34,35,36]. In addition, the DRSA of ethyl acetate fractions of S. fusiforme in our study (IC50 14.61 ± 0.56 μg·mL −1 ) was higher than those of some Sargassaceae species including Halidrys siliquosa (IC50 0.020 ± 3.54 × 10 −4 mg·mL −1 ) [28] and Cystoseira nodicaulis (IC50 14.00 ± 0.04 μg·mL −1 ). When compared with other brown seaweeds, it was lower than that of F. vesiculosus (IC50 4.00 ± 0.01 μg·mL −1 ), similar to that of Himanthalia elongate (IC50 14.00 ± 0.04 μg·mL −1 ), and stronger than that of F. serratus (IC50 14.00 ± 0.04 μg·mL −1 ).…”
Section: Resultsmentioning
confidence: 81%
“…Accumulation of these phloroglucinol-based phenolics contributes to the strong antioxidant activity against free radicalmediated oxidation damage (Kang et al 2012a;Fujii et al 2013). They also show other potential bioactivity such as a bactericidal, antiviral, and anticancer activity and radio protective and antiallergic effects (Li et al 2011;Eom et al 2012;Le Lann et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another study with Halidrys siliquosa (Phaeophyta) showed that the tested extracts presented strong antioxidant activity and a good sunscreen potential, associated with the presence of phlorotannins like diphlorethols, triphlorethols, trifuhalols, and tetrafuhalols [57].…”
Section: Uv-absorbing Compoundsmentioning
confidence: 99%
“…To date, most of these marine-derived compounds were intended for food and pharmaceutical applications [38]. Also, several researchers have been exploring the effects of macroalgae on health, showing some progress and important positive outcomes in regards to some types of cancer; heart diseases; thyroid and immune functions; allergy; inflammation [54]; and antioxidant, antibacterial, and antiviral activity [55], among many others [42,56,57].…”
Section: Macroalgae As a Source Of Bioactive Skin Care Compoundsmentioning
confidence: 99%
See 1 more Smart Citation